MITOCHONDRIAL CYTOCHROME-B AND D-LOOP SEQUENCE BASED GENETIC DIVERSITY IN MAREECHA AND BAREELA CAMEL BREEDS OF PAKISTAN - M. E. Babar; T. Hussain; A. Wajid; A. Nawaz; A. Nadeem; S. A. Shah; M. A. Shahid; N. Ahmad; K. Javed5and M. Abdullah (Journal of Animal and Plant Sciences, 2015)
This is the first study designed on mitochondrial Cytochrome b gene (Cyt-b) and Displacement (D) loop sequence diversity in two camel breeds (Mareecha and Bareela) of Pakistan to assess the status of genetic diversity and differentiation. Genomic DNA was extracted from total of 48 samples (Mareecha = 25 and Bareela = 23). The complete Cyto-b gene sequences (1140bp) analysis showed four parsimony informative sites were at position 137, 146, 337 and 806 and five haplotypes were constructed, indicating low Cyto-b gene genetic variability in selected two Pakistani camel breeds. Analysis of complete mt-DNA D-loop (1214 bp) sequences revealed eight different haplotypes resulting from 32 polymorphic sites (2.63% of all sites), of which 31 sites were singleton variable sites and one site was parsimony informative polymorphic site. The phylogenetic analysis showed two clades of camel (Camelus), dromedary and Bactrian populations that came out as distinct lineage and showed distinct genetic distance between them, and all Pakistani camel haplotypes were clustered with dromedary camels confirmed their genetic architecture as dromedary camels. Genetic variability assessment on camels is important to preserve this genetic resource and to develop future breeding plans to improve camel productivity.
Keywords: Cytochrome b and D-loop; Phylogenetic analysis; Camel breeds; Pakistan